Effect of storage temperature on survival, transmission of Ralstonia solanacearum and quality of potato tubers during storage - DINESH SINGH, RAJESH KUMAR RANJAN*and (Indian Phytopathology, 2016)
Ralstonia solanacearum (Smith, 1896) Yabuuchi et al. (1995) causing brown rot disease is one of the most devastating pathogen of potato. A study was conducted to determine the survivability of R. solanacearum in stored potato and subsequent its transmission in field and quality of potato at different temperature during storage. The potato cvs. Kufri Pukhraj and Kufri Jalandhar were collected from infested field with brown rot from Odisha and Uttarakhand respectively and stored for 6 months at 5 and 15°C temperatures. The study of classical dilution plate technique showed that maximum population of R. solanacearum (cfu log 6.30 / g of tissue) in symptomatic cv. Kufri Pukhraj and followed by cv. Kufri Jalandhar was recorded in samples stored at 15°C. Detection of R. solanacearum was also done through conventional-PCR and bacteria were detected from all symptomatic plants of both cultivars stored at 5 and 15°C whereas bacteria were detected from asymptomatic plant only in Kufri Jalandhar, which was stored at 5oC. The quality of stored potato like TSS, reducing sugar and total sugar of potato tuber gradually increased during storage and the acidity and firmness were found to be gradually declined during storage at all temperatures up to 60 days of storage in both the cultivars.